Reflexivity 3. Breaking out the Reflexive Loop to Decolonise Practice - Simon, Gail (Murmurations: Journal of Transformative Systemic Practice, 2023)
Reflexivity guides our everyday relational ethics but always takes place within a cultural loop. We find what we recognise. Reflexive practice is a commitment to ethical practice but it isn’t a safety net which stops us from reproducing the same dominant discourses of who or what counts and structures which maintain inequalities. In this paper I explore the question, “How can systemic therapists develop reflexivity in their practice to intentionally change and connect personal struggle with wider systems which reproduce power and inequality?” I describe some differences between what I call Reflexivity 1, Reflexivity 2 and Reflexivity 3 to show the impact of ideology on theory, method and what we (think we) notice and act on. I share some reflexive questions, stories from practice and research and examples of wider systemic activism. These working ideas are a response to concerns that the clinic and the organisations which host them are oppressive, colonial structures which limit the progress members of the public can make within them and restrict opportunities to develop practice-theory which takes into account and challenges social, historic and material inequalites and injustice.